Rare bird documentation form for Pine Grosbeak at Ames, 1981 - Dinsmore, James J.et al; Dinsmore, Stephen J.et al (1981)
Rare bird documentation form for a Pine Grosbeak at Ames in Story County, IA on February 28, 1981. Epson - sheet feed